Contested Perspectives on the Social Impacts of a Residential Field Trip. (December 2019) - Gee, Nick
Background: Research into outdoor learning reveals social benefits for trip participants, both individually and collectively. However, this is not universal, and individual participants can experience increased isolation from the wider group.Purpose: This research investigated the underexplored negative experiences of an individual trip participant, in the context of a program promoting collectivist beliefs.Methodology/Approach: An ethnographic methodology was adopted to include full immersion into all aspects of the week-long trip. Data were collected by observation and interviews and analyzed using a conceptual framework around individualism and collectivism.Findings/Conclusions: The teachers perceived the trip as successful, in meeting their collectivist goal of enhancing group cohesion, and data revealed the building of community feelings among the majority of participants, alongside feelings of belonging, togetherness, and mutual support. However, one participant exhibited contrasting individualist perceptions and experiences around interpretations of freedom, privacy, adversity, and cohesion.Implications: Trip leaders need to be mindful of participants as individuals, taking care to neither seek nor project a blanket group identity over all. Within the confines of health and safety and duty of care boundaries, and commensurate with the age range of trip participants, accompanying teachers should understand and respect individual needs within collectivist group socialization agendas.